2012
DOI: 10.1095/biolreprod.111.094110
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Regulates Anti-Mullerian Hormone Expression in Granulosa Cells of the Hen1

Abstract: Anti-Mullerian hormone (AMH) is involved in the regression of the Mullerian ducts in mammalian and avian male embryos as well as the right oviduct in avian female embryos. AMH is expressed by granulosa cells of adult hens and mammals and is thought to be involved in the recruitment of follicles from the primordial pool as well as in regulating follicle-stimulating hormone (FSH) sensitivity. We have shown that AMH expression by the granulosa layer of hens is high in the small follicles but decreased in the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 37 publications
1
30
0
3
Order By: Relevance
“…High-dose VD3 appeared to have a greater impact than low-dose VD3 on promoting later folliculogenesis by improving small antral follicle growth. The data were consistent with findings in hens in which a significant enhancement of cell proliferation was observed for non-luteinized granulosa cells incubated with VD3 (17). A previous study indicated that a relative high-dose VD3 not only down-regulated AMH receptor II gene expression, but also significantly reduced the phosphorylation and nuclear localization of SMAD 1/5/8, which are critical for AMH signaling, in cultured granulosa cells collected from IVF patients (20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High-dose VD3 appeared to have a greater impact than low-dose VD3 on promoting later folliculogenesis by improving small antral follicle growth. The data were consistent with findings in hens in which a significant enhancement of cell proliferation was observed for non-luteinized granulosa cells incubated with VD3 (17). A previous study indicated that a relative high-dose VD3 not only down-regulated AMH receptor II gene expression, but also significantly reduced the phosphorylation and nuclear localization of SMAD 1/5/8, which are critical for AMH signaling, in cultured granulosa cells collected from IVF patients (20).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies suggested that FSH was a survival factor for preantral follicles developed in vitro in both nonhuman primates and humans (15, 16). Although not demonstrated in primate species, FSH receptor mRNA expression was up-regulated in non-luteinized granulosa cells in hens following VD3 treatment in culture (17). Therefore, exogenous VD3 may increase FSH sensitivity in macaque follicles, and thereby promote follicle survival in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…VitD increased AMH mRNA in prostate cancer cells were a VDRE site was detected (Malloy et al 2009). Conversely, VitD decreased AMH mRNA in primary granulosa cells from hens (Wojtusik & Johnson 2011). In a study with primary human granulosa cells, 1α,25(OH) 2 D decreased AMH receptor II and FSH receptor mRNA expression, while promoting 3β-HSD expression and activity leading to increased progesterone secretion (Merhi et al 2014) (Fig.…”
Section: R36mentioning
confidence: 89%
“…Thus, the observation that many small follicles grow in PCOS may be explained by excess testosterone. Alternatively, 1,25D 3 might inhibit the testosterone-stimulated early stages of follicular growth because 1,25D 3 is known to inhibit the proliferation and induce the differentiation of a variety of cells [48], and VDR is expressed in the granulosa cells of largest follicle [49]. It is possible that 1,25D 3 paired with testosterone preferentially improves the growth of larger follicles.…”
Section: Discussionmentioning
confidence: 99%